Pengaruh Budgetary Slack Terhadap Budget Participation dengan Dimoderasi Information Asymetry dan Budget Emphasis - Ardiani Ika Sulistyawati; Yulianti Yulianti; Edy Mulyantomo (Politeknik Ganesha Medan, 2023)
This study aims to analyze the effect of budgetary participation on budgetary slack by moderating information asymmetry and budget emphasis. The existence of a research gap is the basis for conducting this research. This research is categorized as a survey research, where the research instrument is a questionnaire. The population in this study were structural officials in the SKPD of the 24 Kendal City Offices. The subjects in this study were the head of the department, the secretary, the head of the finance sub-section, the head of the planning sub-section, and staff at the Kendal Regency Government. The sampling technique used the census method where all employees of the finance department at the Kendal City SKPD had the same opportunity to become respondents in this study. The results of the study indicate that budgetary participation has an influence on Budgetary Slack. This study also proves empirically that information asymmetry and budget emphasis are able to moderate the effect of budget participation on budgetary slack.